Dissolution profile evaluation of selected brands of amoxicillin-clavulanate potassium 625 mg tablets retailed in Hawassa town, Sidama Regional State, Ethiopia - Eyob Endashaw; Ramanjireddy Tatiparthi; Tesfaye Mohammed; Henok Teshome; Markos Duguma; Yesuneh Tefera (SpringerOpen, 2024)
Abstract Poor quality amoxicillin-clavulanate potassium tablets have been recently discovered in generic drugs related to Augmentin-like medicines containing amoxicillin and clavulanic acid, as well as its derivatives containing falsified active ingredients. One of the most important dosage form characteristics are a detailed active pharmaceutical ingredients dissolution release profile evaluation obtained through dissolution testing. The dissolution test is used in the development of both brand-name and generic drugs. Prior to beginning bioequivalence studies, it is critical to compare the dissolution profiles of various pharmaceutical products. As a result, dissolution is a critical quality control parameter for drugs because it has a direct impact on absorption of pharmaceutical products. Dissolution profile evaluation of seven brands of amoxicillin-clavulanate potassium tablets is retailed in Hawassa town, Sidama Regional State, Ethiopia. The seven brands of amoxicillin-clavulanate potassium tablets were collected from Hawassa town, Sidama Regional State, Ethiopia. The dissolution study was conducted as per USP40-NF35. Then, the dissolution profile test results were compared by one-way ANOVA Dunnett's test, model independent, and model dependent method. All of the included brand tablets complied with a single-point dissolution study specification. All brand tablets had similar dissolution profiles (p > 0.05), difference factor (f1) < 15%, and dissolution efficiency $$(\le 10\varvec{%}$$ ( ≤ 10 % ). However, the f2 (similarity factor) value justifies that all brand tablets were not within USFDA specification ( $$\ge$$ ≥ 50%). The evaluated brands followed the Korsemeyer-Peppas followed by the Weibull curve models. All brand tablets passed the single point USP dissolution specification and the USFDA therapeutic interchangeability guideline. The similarity factor (f2), on the other hand, confirmed that none of the tested brand tablets were interchangeable with the innovator product. Therefore, researchers, national medicine regulatory bodies, and the manufacturer should conduct a properly designed dissolution test as proof of an in vitro bioequivalence study supported by in vivo bioavailability data.